Effect of antioxidants and exercise on bone metabolism - Maimoun, L.; Simar, D.; Caillaud, C.; Peruchon, E.; Sultan, C.; Rossi, M.; Mariano-Goulart, D. (Journal of Sports Sciences, 2008)
We examined the effects of antioxidant supplementation in association with progressive aerobic training on the bone metabolism of healthy elderly individuals. For 8 weeks, 13 participants (mean age 74 years) received vitamin C (500 mg) and vitamin E (100 mg) daily and participated in a supervised progressive aerobic training programme. After the 8 weeks, 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D concentrations were increased significantly by 42.8% (P < 0.001) and 26.8% (P < 0.01) respectively, while parathyroid hormone concentration was decreased by 17.5% (p < 0.05). Of the bone markers, only bone alkaline phosphatase decreased, by 14.6% (P < 0.05). No variation was observed for ionized calcium, insulin-like growth factor-1 or insulin-like growth factor binding protein-3. Our findings suggest that 8 weeks of combined antioxidant supplementation and aerobic training modified vitamin D metabolism and parathyroid hormone concentration. These adaptations might counterbalance the unfavourable hormonal profile frequently observed in the elderly that predisposes them to accentuated age-related bone loss.